An Assessment of the Role of Fiber Coating and Suspending Fluid on the Deposition of Carbon Nanotubes onto Glass Fibers for Multiscale Composites1 . Issue 6 (19th November 2015) - Ku‐Herrera, J. J.; May‐Pat, A.; Avilés, F.
Abstract : Multiwall carbon nanotubes (MWCNTs) were ultrasonically deposited onto glass fibers by using either distilled water or a hydrolyzed silane. The role of the fiber coating (sizing) was investigated by depositing MWCNTs onto glass fibers with and without sizing. The interfacial shear strength (IFSS) between the MWCNT‐modified fibers and a vinyl ester matrix was analyzed by the microbond test. Increased electrical conductivity and surface roughness was achieved upon MWCNT deposition on the fibers. The use of a silane as suspending fluid renders moderate benefits with respect to distilled water, and its role is more critical in improving the IFSS between the MWCNT‐modified fibers and the matrix. Abstract : Increased glass fiber electrical conductivity and improved interfacial shear strength between the CNT‐modified fibers and a vinyl ester resin is achieved upon CNT deposition, especially when the fiber coating is maintained and an adequate silane coupling agent is used.